2015
DOI: 10.14573/altex.1502181
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive instant genotyping of fluorescently labeled transgenic mice

Abstract: SummaryFluorescence proteins have been useful as genetic reporters for a wide range of applications in biomedical research and are frequently used for the analysis of transgene activity. Here, we show that expression levels of the ubiquitously expressed fluorescent proteins eGFP, mCherry and tdTomato can be measured in transgenic mouse lines with random or targeted integrations. We identified the tail of the mouse as the tissue best suited for quantifying fluorescence intensity and show that expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…After breeding and application of a previously established novel non-invasive genotyping procedure for fluorescently labelled transgenic mice [27], we noticed the absence of viable homozygous UbC-mCherry transgenic mice (first described in [24]) in the offspring of hemizygous × hemizygous matings (see Figure 1A and Table 1). To eliminate any possibility of mCherry toxicity at high expression levels, we compared the overall expression levels (fluorescence efficiency) to the viable CAG-mCherry hemizygous and homozygous transgenic mice (first described in [27]) that is approximately 5-fold and 9-fold higher, respectively, compared to hemizygous UbC-mCherry transgenic mice ( Figure 1A). It has been reported that lentiviral vector-mediated transgenesis frequently leads to integrations in the middle of transcribed regions and thereby induces insertional mutations in endogenous genes [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After breeding and application of a previously established novel non-invasive genotyping procedure for fluorescently labelled transgenic mice [27], we noticed the absence of viable homozygous UbC-mCherry transgenic mice (first described in [24]) in the offspring of hemizygous × hemizygous matings (see Figure 1A and Table 1). To eliminate any possibility of mCherry toxicity at high expression levels, we compared the overall expression levels (fluorescence efficiency) to the viable CAG-mCherry hemizygous and homozygous transgenic mice (first described in [27]) that is approximately 5-fold and 9-fold higher, respectively, compared to hemizygous UbC-mCherry transgenic mice ( Figure 1A). It has been reported that lentiviral vector-mediated transgenesis frequently leads to integrations in the middle of transcribed regions and thereby induces insertional mutations in endogenous genes [31].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the identification of the mutated endogenous gene, we suggest a renaming of the line according to the MGI Guidelines for Nomenclature for insertional mutations as B6(Cg)-Tyrc-2J Ing3 Tg(UBC-mCherry)1Phbs/J . A second red fluorescence reporter mouse line, which was used as a control for quantification of mCherry expression, designated as C57BL/6NCrl-Tg(CAG-mCherry)690Biat, was also described previously [27]. For reconstitution of the Ing3 mutation, an Ing3-P2A-eGFP expressing transgenic mouse line, designated C57BL/6N-TgTn(sb-CAG-Ing3-P2A-eGFP)774.1Biat was produced by transposon technology [28] and subsequent Cre mediated excision of a stop cassette (described in detail in Fink et al, manuscript in preparation).…”
Section: Animal Husbandry Breeding Embryo Production and Quantitatmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vivo imaging of whole animals, mice were shaved from the neck to the lower torso. Animals were next placed in the IVIS Imaging System and analyzed for fluorescence using excitation and emission wavelengths of 405–485 and 625 nm, respectively ( 25 ). Data were collected in units of photons/sec/cm 2 and visualized using Living Image software v2.50 (Xenogen Corporation).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, X chromosome inactivation in mammals during embryologic development 811 could terminate the expression of the X-linked transgene 7 . As one type of non-invasive genetic reporter, fluorescence proteins have been applied in many fields of research, such as identifying the genotype of transgenic animals 1214 , tracing a specific cell lineage 15,16 , and studying the expression status of genes in time and space 7,17,18 . Therefore, non-invasive genetic reporters inspired us to consider how to use a non-invasive label to sex mammalian embryos.…”
Section: Introductionmentioning
confidence: 99%